9(2k+3)+2=11(k-6)

Simple and best practice solution for 9(2k+3)+2=11(k-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2k+3)+2=11(k-6) equation:


Simplifying
9(2k + 3) + 2 = 11(k + -6)

Reorder the terms:
9(3 + 2k) + 2 = 11(k + -6)
(3 * 9 + 2k * 9) + 2 = 11(k + -6)
(27 + 18k) + 2 = 11(k + -6)

Reorder the terms:
27 + 2 + 18k = 11(k + -6)

Combine like terms: 27 + 2 = 29
29 + 18k = 11(k + -6)

Reorder the terms:
29 + 18k = 11(-6 + k)
29 + 18k = (-6 * 11 + k * 11)
29 + 18k = (-66 + 11k)

Solving
29 + 18k = -66 + 11k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-11k' to each side of the equation.
29 + 18k + -11k = -66 + 11k + -11k

Combine like terms: 18k + -11k = 7k
29 + 7k = -66 + 11k + -11k

Combine like terms: 11k + -11k = 0
29 + 7k = -66 + 0
29 + 7k = -66

Add '-29' to each side of the equation.
29 + -29 + 7k = -66 + -29

Combine like terms: 29 + -29 = 0
0 + 7k = -66 + -29
7k = -66 + -29

Combine like terms: -66 + -29 = -95
7k = -95

Divide each side by '7'.
k = -13.57142857

Simplifying
k = -13.57142857

See similar equations:

| 14x+1-12x-6=1 | | f(x)=2x^2+8x+5 | | 84=-8x-4 | | 8(4k-4)=-5k-34 | | 5(2x+1)=3(2x+7) | | 10(1)=-10 | | 2v+4v=36 | | -7p-1=1 | | 5-(-7)=-12 | | Y=x^4+x^3-12x^2+2x+8 | | 8y-9=3y+2 | | (5x+7)(3x^2-13x+12)=0 | | 21-14=7 | | -3=9-3x | | 2(3x+1)+4x+4 = 26 | | 4z=8(z-5)-16 | | 16x^2+64x+39=0 | | -n+5(n+8)=8(n+2) | | -5x-6+24x=21 | | 40=.012x^2-.543x+35.724 | | 293=46-x | | 3x-12+2x=-3x+14 | | 0.25+0.8x=0.55 | | 30=(.5)(b)(10) | | -(6-6n)=6(n+6) | | 79=2e^4x | | x-37+2x=36+2(x+1) | | 2(-1-3v)-2=6+8(6v-8) | | 0.25+0.8=0.55 | | -7(x+6)=-5(8+x)-4 | | 5x^2+57X=36 | | 6y-2x=0 |

Equations solver categories